Postcard from Otto Dimroth to Georg Bredig, October 1917 - Dimroth, Otto (1917)
Postcard from Otto Dimroth (1872-1940) to Georg Bredig (1868-1944) in which he thanks Bredig for his words of congratulations. Otto Dimroth, the father of chemist Karl Dimroth (1910-1995), was a German scientist. He is the inventor of the Dimroth Condenser and discovered the Dimroth rearrangement reaction.
Keywords: Bredig, Georg, 1868-1944; Dimroth, Otto, 1872-1940; Chemists; Condensers (Vapors and gases); Chemistry, Organic